The relationship between improved elderly nutritional risk index and short-term all-cause mortality in patients with urinary sepsis: a retrospective cohort study - Liu, Rui; Li, Wei; Wei, Xi; Sun, Fa; Li, Tao (Frontiers in Nutrition, 2026)
BackgroundThe modified Geriatric Nutritional Risk Index (mGNRI) is a simple, objective tool for assessing malnutrition risk. Its potential utility in patients with urosepsis, however, remains insufficiently explored.MethodsWe conducted a retrospective study of patients with sepsis secondary to urinary tract infections using data from the Medical Information Mart for Intensive Care (MIMIC-IV) database and a cohort from the Affiliated Hospital of Guizhou Medical University. The association between the mGNRI and short-term adverse outcomes was examined using restricted cubic spline (RCS) regression, multivariate Cox proportional hazards regression, Kaplan–Meier survival curves, and subgroup analyses. Furthermore, multivariate Cox regression was employed to evaluate the incremental predictive value of mGNRI when integrated with conventional critical illness scores.ResultsThis study included 1,875 patients with urosepsis. The 28-day ICU and in-hospital mortality rates were 15.5 and 14.3%, respectively. In fully adjusted models, both the continuous and categorical mGNRI were significantly associated with 28-day mortality. For each one-unit increase in the continuous mGNRI, the hazard ratios (HRs) for ICU and in-hospital mortality were 0.98 (95% CI: 0.97–0.99) and 0.98 (95% CI: 0.96–0.99), respectively. Similarly, for each one-standard deviation (SD) increase, the HRs were 0.83 (95% CI: 0.73–0.94) for ICU mortality and 0.81 (95% CI: 0.70–0.93) for in-hospital mortality. When using the no-risk group as a reference, the high-risk group exhibited significantly increased mortality, with HRs of 1.55 (95% CI: 1.07–2.24) for ICU death and 1.59 (95% CI: 1.08–2.32) for in-hospital death. RCS analysis revealed a negative linear relationship between the continuous mGNRI and mortality. Furthermore, subgroup and interaction analyses demonstrated that this association remained consistent across nearly all predefined subgroups. All findings were subsequently validated in an external, real-world cohort.ConclusionOur findings indicate that the mGNRI serves as a significant inverse predictor of short-term mortality risk in patients with urosepsis. It demonstrates potential as a practical stratification tool to help clinicians identify high-risk patients early for targeted interventions.